2017
DOI: 10.1002/ccd.27366
|View full text |Cite
|
Sign up to set email alerts
|

Procedural trends, outcomes, and readmission rates pre‐and post‐FDA approval for MitraClip from the National Readmission Database (2013–14)

Abstract: A significant increase in MitraClip procedural volumes occurred post-FDA approval. Overall morbidity and mortality were low and trended downwards. Hospital procedure volume ≥10 cases were associated with lower mortality and overall complication rates. These data suggest a successful roll out of a very complex novel structural heart procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
17
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
3
17
1
Order By: Relevance
“…Approximately half of all 30‐day readmissions following TMVR or SMVR were for cardiac reasons. Consistent with prior studies, we found heart failure followed by arrhythmias to be the most common cardiac causes for readmissions in patients undergoing TMVR . Partial clip detachment has been previously raised as a concern for procedural complications in the early period after TMVR, which may play a role with resurgence of heart failure symptoms among TMVR patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Approximately half of all 30‐day readmissions following TMVR or SMVR were for cardiac reasons. Consistent with prior studies, we found heart failure followed by arrhythmias to be the most common cardiac causes for readmissions in patients undergoing TMVR . Partial clip detachment has been previously raised as a concern for procedural complications in the early period after TMVR, which may play a role with resurgence of heart failure symptoms among TMVR patients.…”
Section: Discussionsupporting
confidence: 89%
“…This may be because SMVR is a more invasive procedure and therefore associated with higher rates of in‐hospital complications and longer recovery, as seen in our study. Furthermore, other investigations utilizing the NRD have demonstrated 30‐day readmission rates of 14.6–15.1% following TMVR during 2013–2014, compared with 11.6% observed in our study. This suggests a 3.0–3.5% decrease in 30‐day readmission rates when compared to our study's 2014–2015 timeframe, which may be related to increased experience and procedure volume since prior studies have shown a trend towards reduced readmissions after TMVR with increased operator experience .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In patients with high risk of operative morbidity and mortality for surgical mitral valve repair/replacement, transcatheter mitral valve repair (TMVR) in the form of MitraClip offers a safe and effective alternative . Moreover, this technique can lead to effective reduction of both degenerative (primary) and secondary (functional) forms of mitral regurgitation .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Catheterization and Cardiovascular Interventions , Panaich et al aimed to study in‐hospital mortality and procedural complications, in addition to 30‐day readmission rates, associated with the commercialization of MitraClip pre‐ and post FDA approval . The investigators used ICD‐9 diagnosis codes to search the National Readmission Database and retrospectively analyze the data from an estimated 2,003 patients who underwent MitraClip in the two years between January 2013 and November 2014.…”
mentioning
confidence: 99%